Step-by-step explanation:
Answer:
60
Step-by-step explanation:
Replace c and d with -5 and 6.
-2*-5*6
-2*-5=10
10*6=60
The expression is equal to 60.
-hope it helps
<span>6m + 1 = 23
Reorder the terms:
1 + 6m = 23
Solving
1 + 6m = 23
Solving for variable 'm'.
Move all terms containing m to the left, all other terms to the right.
Add '-1' to each side of the equation.
1 + -1 + 6m = 23 + -1
Combine like terms: 1 + -1 = 0
0 + 6m = 23 + -1
6m = 23 + -1
Combine like terms: 23 + -1 = 22
6m = 22
Divide each side by '6'.
m = 3.666666667
Simplifying
m = 3.666666667 i think</span>
Answer:
A. 8
Step-by-step explanation:
Because the table is going by 8's so that's why the answer is A.8